Effect of Group Resume on Motivation and Learning Outcomes at SDN Perumnas 1 Subang - Muiz Fahmi Septiana; Ifah Khadijah (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the effect of the cooperative learning model of Group Resume on students’ motivation and learning outcomes in Islamic Religious Education (IRE) at SDN Perumnas 1 Subang. The study employed a quantitative approach with a quasi-experimental design, comparing class 5B as the experimental group implementing Group Resume and class 5A as the control group, consisting of 16 and 20 students, respectively. Data were collected using a learning motivation questionnaire and a learning outcomes test, and analyzed descriptively and inferentially using an independent samples t-test. The results indicate that the average motivation and learning outcomes of students in the experimental class were higher than those in the control class, with statistically significant differences. These findings support hypotheses H1 and H2, confirming that Group Resume positively affects both students’ motivation and learning outcomes in IRE. The method encourages active participation, social interaction, idea exchange, and the development of students’ critical thinking skills. The study implies that Group Resume is effective in creating a collaborative and interactive learning environment and can serve as a reference for educators to improve the quality of learning and student motivation in elementary schools.